2021
DOI: 10.1007/s11356-021-14853-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term copper exposure promotes apoptosis and autophagy by inducing oxidative stress in pig testis

Abstract: Copper (Cu) is a heavy metal which is being used widely in the industry and agriculture. However, the overuse of Cu makes it a common environmental pollutant. In order to investigate the testicular toxicity of Cu, the pigs were divided into three groups and were given Cu at 10 (control), 125, and 250 mg/kg body weight, respectively. The feeding period was 80 days. Serum hormone results showed that Cu exposure decreased the concentrations of follicular stimulating hormone (FSH) and luteinizing hormone (LH) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…This finding indicated the occurrence of oxidative stress in the testicular tissue. The results of [ 26 ] showed that the results obtained after exposing pigs to 125 and 250 mg/kg of copper in the form of copper sulphate for 80 days were consistent with the results in the present study, i.e., the levels of MDA increased, and apoptosis and autophagy were promoted in the testes.…”
Section: Resultssupporting
confidence: 91%
“…This finding indicated the occurrence of oxidative stress in the testicular tissue. The results of [ 26 ] showed that the results obtained after exposing pigs to 125 and 250 mg/kg of copper in the form of copper sulphate for 80 days were consistent with the results in the present study, i.e., the levels of MDA increased, and apoptosis and autophagy were promoted in the testes.…”
Section: Resultssupporting
confidence: 91%
“…However, its extensive usage in many enterprises, such as, electronics, pesticides, building and transportation materials, water pipes and others incurred a notable eco-environmental contamination by polluting land and water resources [ 5 , 6 , 57 ]. Exposure to Cu compounds has been associated with adverse effects, including testicular oxidative stress, and apoptosis, along with declined sperm quality [ 19 , 24 ]. CUR has shown potent antioxidant properties and protected the testis against injury induced by various agents [ 26 , 27 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of Cu on male fertility are not fully understood, excessive reactive oxygen species (ROS) and oxidative stress could play a significant role [19,24]. Given its rich content of highly unsaturated fatty acids, the testis is vulnerable to oxidative injury [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cumulative studies reveal that autophagy is a double-edged sword [ 25 ]. Autophagy disorder may also promote cytopathy, decreased serum testosterone, and cause sperm differentiation defects [ 26 ]. Thus, oxidative stress-induced autophagy is considered one of the proposed mechanisms for idiopathic male infertility [ 27 ].…”
Section: Introductionmentioning
confidence: 99%